2013
DOI: 10.1111/pce.12197
|View full text |Cite
|
Sign up to set email alerts
|

Lack of photosynthetic or stomatal regulation after 9 years of elevated [CO2] and 4 years of soil warming in two conifer species at the alpine treeline

Abstract: Alpine treelines are temperature-limited vegetation boundaries. Understanding the effects of elevated [CO2] and warming on CO2 and H2O gas exchange may help predict responses of treelines to global change. We measured needle gas exchange of Larix decidua Mill. and Pinus mugo ssp. uncinata DC trees after 9 years of free air CO2 enrichment (575 µmol mol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 49 publications
14
61
0
Order By: Relevance
“…In addition, the temperature increase in the present experiment was relatively minor (approximately 3°C), which may have been insufficient to affect the composition and balance of inorganic carbon in the water column and thus may have further influenced the utilization of inorganic carbon in V. natans. A recent study produced similar results, indicating that soil warming had little effect on the gas exchange of plants at the alpine treeline (Streit et al 2014). The individual ramet biomass of V. natans decreased with elevated temperature, but only significantly at ambient CO 2 .…”
Section: Discussionmentioning
confidence: 51%
“…In addition, the temperature increase in the present experiment was relatively minor (approximately 3°C), which may have been insufficient to affect the composition and balance of inorganic carbon in the water column and thus may have further influenced the utilization of inorganic carbon in V. natans. A recent study produced similar results, indicating that soil warming had little effect on the gas exchange of plants at the alpine treeline (Streit et al 2014). The individual ramet biomass of V. natans decreased with elevated temperature, but only significantly at ambient CO 2 .…”
Section: Discussionmentioning
confidence: 51%
“…More detailed information can be derived from the individual carbohydrates (sucrose, glucose, and fructose), and sugar alcohols (e.g., pinitol), but also from compounds like organic acids (malate and citrate) that are involved in more "downstream metabolic processes" leading to systematic but varying 13 C-enrichment of sink organs (such as stem) in comparison to leaves [20]. Thus far, there have been few investigations analyzing δ 13 C of individual carbohydrates and organic acids [19][20][21][22][23][24][25][26] using high-performance liquid chromatography (HPLC). However, even fewer investigations were applied in natural forest ecosystems to address questions of tree eco-physiology [19,22,23,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, there have been few investigations analyzing δ 13 C of individual carbohydrates and organic acids [19][20][21][22][23][24][25][26] using high-performance liquid chromatography (HPLC). However, even fewer investigations were applied in natural forest ecosystems to address questions of tree eco-physiology [19,22,23,26,27]. Therefore, further studies are needed to understand how environmental changes impact δ 13 C values and concentrations of individual compounds at the leaf level in declining trees.…”
Section: Introductionmentioning
confidence: 99%
“…Some works conducted at some trees grown in Swiss Alps (2,180 m a.s.l.) have shown that the CO 2 -induced increase in photosynthesis has been maintained, and the initial increase in growth rate has also been sustained in Larix deciduas (Handa et al 2006;Dawes et al 2013;Streit et al 2014). Downward adjustment of photosynthetic capacity by -26 % on average under long-term exposure to elevated CO 2 has been observed in Swiss Alps (2,440 m a.s.l., Inauen et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Given that CO 2 is the primary substrate for photosynthesis, detailed information on how elevated CO 2 affects leaf level is critical to understand the effects of climate change on the structure, function, and productivity of forest ecosystems (Leakey et al 2009;Han et al 2011). A few studies have focused on the responses of trees growing in high-elevation (HE) areas to elevated CO 2 (Dawes et al 2013;Streit et al 2014). Some works conducted at some trees grown in Swiss Alps (2,180 m a.s.l.)…”
Section: Introductionmentioning
confidence: 99%